Vincent van Gogh. The Letters - Van Gogh Museum (2009)
[Dt.:] Die Online-Datenbank "Vincent van Gogh. The Letters" ermöglicht zum ersten Mal die Recherche des gesamten Briefwechsels von Vincent van Gogh (1853-1890). Jeder der 902 Briefe ist im Original abgebildet und wird von einer Transkriptionen, englischen Übersetzungen, sowie Notizen und Abbildungen ergänzt. Die Briefe können nach Zeitraum, Korrespondent oder Ort, sowie Briefe mit Skizzen durchsucht werden. Neben einer Einfachen Suche wird eine Erweiterte Suche angeboten. Zudem gibt es u. a. eine ausführliche Beschreibung des Projektes, des Künstlers als Brief-Autor, seiner Korrespondenten, des biographisch und historischen Kontextes und eine biographische Chronologie. - [Engl.:] The online-database "Vincent van Gogh. The Letters" for the first offers the entire correspondence of Vincent van Gogh (1853-1890). Every one of the 902 letters is depicted in its original form and is supplemented by a transcription, an English translation, as well as notes and images. The letters can be searched by period, correspondent, place and additionally by letters with sketches. Besides a simple search category the database offers an advanced search option. Furthermore, the website holds a detailed introduction to the projects itself, to the artist s letters, to the correspondents, the biographical and historical context and provides a biographical chronology.